Computer Science &Amp; Information Technology (CS &Amp; IT) 2018
DOI: 10.5121/csit.2018.81004
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Classifier and Analysis for Epidemic Prediction

Abstract: Intelligent Models for predicting diseases whether building a model to help the doctor or even preventing its spread in an area globally, is increasing day by day. Here we present a noble approach to predict the disease prone area using the power of Text Analysis and Machine Learning. Epidemic Search model using the power of the social network data analysis and then using this data to provide a probability score of the spread and to analyse the areas whether going to suffer from any epidemic spread-out, is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The word clouds represent the image of text, where the size of the phrase is proportionate to the prevalence of occurrence. Therefore, the more prominent phrase expresses the most frequent words posted in tweets [51]. At a glance, the word cloud of COVID-19 vaccine shows more common words discussed by Sentiment_Type object people such as "Covid-vaccine", "Russia", "First Covid", "people", and "coronavirus", "trial", and "health ministry".…”
Section: Data Visualizationmentioning
confidence: 99%
“…The word clouds represent the image of text, where the size of the phrase is proportionate to the prevalence of occurrence. Therefore, the more prominent phrase expresses the most frequent words posted in tweets [51]. At a glance, the word cloud of COVID-19 vaccine shows more common words discussed by Sentiment_Type object people such as "Covid-vaccine", "Russia", "First Covid", "people", and "coronavirus", "trial", and "health ministry".…”
Section: Data Visualizationmentioning
confidence: 99%
“…Sentiment analysis has been applied to predict the evolution of the stock market [7], or to predict commercial success based on sentiments from hotel reviews [8], movie reviews [9], or restaurant reviews [9], or to predict risk phenomena, e.g. crime [10] or epidemic outbreaks [11].…”
Section: Sentiment Analysismentioning
confidence: 99%
“…Ishtiaq Ahmed et al [13] have suggested a hybrid SMS classification system for detecting harm or spam, through the use of the Apriori algorithm and Naïve Bayes classifier. Even though this approach is fully logic-based, the performance of the method depends on the database's statistical character.…”
Section: Related Workmentioning
confidence: 99%